Measures of body habitus are associated with lung function in adults with cystic fibrosis: a population-based study - Forrester, Doug L.; Knox, Alan J.; Smyth, Alan R.; Fogarty, Andrew W. (Elsevier, 2013)
Background Body habitus differences may explain some of the variation in lung function between individuals with cystic fibrosis (CF). We tested the hypothesis that measures of lean muscle mass and obesity are independently associated with lung function in CF.